Social Work Practice in the Aftermath of Natural Disasters: A Qualitative Inquiry in the Sultanate of Oman - Al Maamari, Raya Hamed Hilal (2023)
Climate change and increasingly extreme weather have caused a surge in natural disasters over the past 50 years. Oman is frequently exposed to tropical cyclones and storms, but very little empirical research exists on natural disasters, nor on the social work responses to those situations, a gap which motivated this research. The study is designed to explore social work practice in the aftermath of natural disasters in Oman; it conducted 43 semi-structured interviews with social workers, NGO workers, religious practitioners and people affected by disasters. A wide-ranging theoretical framework underpins the study, and includes Maslow's hierarchy of needs, the multi-capital approach, concepts of vulnerability and resilience, and the case management approach. The findings illustrate the impact of natural disasters on individuals, families and communities, and also the provision of material, financial, psychosocial, and spiritual support services. They show that while there are efforts to provide material and financial support, several issues need to be considered. More attention is also needed regarding the provision of psychosocial and spiritual support. The thesis also reviews the knowledge, skills, and values necessary for social workers to perform their roles effectively. The conclusion highlights the conceptual and theoretical implications of the findings, in order to develop more effective social work practice in response to natural disasters in Oman.